Integrating artificial intelligence into medical curricula: perspectives of faculty and students in South Korea - Suyoun Kim; Su Hyun Kim; Hansea Kim; Young-Mee Lee (Korean Journal of Medical Education)
Purpose With the accelerated adoption of artificial intelligence (AI) in medicine, the integration of AI education into medical school curricula is gaining significant attention. This study aimed to gather the perceptions of faculty members and students regarding the integration of AI education into medical curricula in the Korean context. Methods Faculty members and medical students’ perspectives on integrating AI into medical curricula were assessed through thematic analysis of free-written responses from 157 faculty members and 125 students in a national online survey on medical AI competencies in South Korea. Results Three key themes emerged: content, which prioritizes basic knowledge and its practical applications, with an emphasis on ethical and legal responsibilities; curricular design, which advocates for a spiral curriculum tailored to learners' needs; and concerns, which highlight balancing AI integration with the principal goals of medical education while critically evaluating ongoing advancements. Conclusion Our study adds valuable insights into the content and methods to prioritize AI education. Given the rapid evolution of medical learners and AI technologies, continuous and timely needs assessment for AI curriculum development is crucial to maintain relevance and effectiveness.